Virus-like particle vaccine with B-cell epitope from porcine epidemic diarrhea virus (PEDV) incorporated into hepatitis B virus core capsid provides clinical alleviation against PEDV in neonatal piglets through lactogenic immunity. Issue 33 (14th July 2020) - Lu, Yi; Clark-Deener, Sherrie; Gillam, Frank; Heffron, Connie Lynn; Tian, Debin; Sooryanarain, Harini; LeRoith, Tanya; Zoghby, Jessica; Henshaw, Mallori; Waldrop, Steven; Pittman, Jeremy; Meng, Xiang-Jin; et al.
Abstract: Porcine epidemic diarrhea virus (PEDV) has had a negative economic impact on the global swine industry for decades since its first emergence in the 1970s in Europe. In 2013, PEDV emerged for the first time in the United States, causing immense economic losses to the swine industry. Efforts to protect U.S. swine herds from PEDV infection and limit PEDV transmission through vaccination had only limited success so far. Following the previous success in our virus-like particle (VLP) based vaccine in mouse model, in this study we determined the immunogenicity and protective efficacy of a VLP-based vaccine containing B-cell epitope 748 YSNIGVCK 755 from the spike protein of PEDV incorporated into the hepatitis B virus core capsid (HBcAg), in a comprehensive pregnant gilt vaccination and piglet challenge model. The results showed that the vaccine was able to induce significantly higher virus neutralization response in gilt milk, and provide alleviation of clinical signs for piglets experimentally infected with PEDV. Piglets from pregnant gilt that was vaccinated with the VLP vaccine had faster recovery from the clinical disease, less small intestinal lesions, and higher survival rate at 10 days post-challenge (DPC).